Healthcare resources, organisational support and practice in asthma in six public health clinics in Malaysia - Hussein, Norita; Ramli, Rizawati; Su, May Liew; Hanafi, Nik Sherina; Ping, Yein Lee; Ai, Theng Cheong; Shariff-Ghazali, Sazlina; Mohd Ahad, Azainorsuzila; Patel, Jaiyogesh; Schwarze, Jürgen; Ee, Ming Khoo (Nature Publishing Group, 2023)
Asthma, a common chronic respiratory illness is mostly managed in primary care. We aimed to determine healthcare resources, organisational support, and doctors’ practice in managing asthma in a Malaysian primary care setting. A total of six public health clinics participated. We found four clinics had dedicated asthma services. There was only one clinic which had a tracing defaulter system. Long-term controller medications were available in all clinics, but not adequately provided. Resources, educational materials, and equipment for asthma management were present, though restricted in number and not placed in main locations of the clinic. To diagnose asthma, most doctors used clinical judgement and peak flow metre measurements with reversibility test. Although spirometry is recommended to diagnose asthma, it was less practiced, being inaccessible and unskilled in using as the main reasons. Most doctors reported providing asthma self-management; asthma action plan, but for only half of the patients that they encountered. In conclusion, there is still room for improvement in the provision of clinic resources and support for asthma care. Utilising peak flow metre measurement and reversibility test suggest practical alternative in low resource for spirometry. Reinforcing education on asthma action plan is vital to ensure optimal asthma care.